Spiritual Emotional Freedom Technique (SEFT) untuk Menurunkan Tekanan Darah pada Penderita Hipertensi: Tinjauan Sistematis: Spiritual Emotional Freedom Technique (SEFT) to Lower Blood Pressure in Hypertension Sufferers: A Systematic Review - Jumain; Agustinus Talindong; Wahyu; Parmi; Mutmainnah HS (Journal of Health (JoH), 2024)
Spiritual Emotional Freedom Technique (SEFT) is a technique that combines body system techniques and spiritual therapy using pressure on certain points on the body. SEFT includes helping individuals free from emotional stress (negative energy), which is the cause of increasing blood pressure in hypertensive patients. Hypertension is a condition where there is an increase in blood pressure, characterized by symptoms that will progress to a target organ, such as stroke, coronary heart disease and right ventricular hypertrophy. This systematic review aims to assess the effects of the Spiritual Emotional Freedom Technique (SEFT) with the result of reducing blood pressure in hypertensive sufferers. Using a systematic review by utilizing four electronic databases for searching: Pubmed, Science Direct, Google Scholar and Garuda Portal. Randomized Control Trial and Quasy Experiment studies that conducted research on SEFT were used as inclusion criteria. This systematic review contained ten studies meeting the criteria for a full text review. The findings in this study show that SEFT is very effective in reducing blood pressure in people with hypertension. Non-pharmacological intervention, namely SEFT (Spiritual Emotional Freedom Technique), has a good impact on hypertension to reduce blood pressure. So, it can be used as a good complementary therapy for hypertension sufferers.